Pengaruh Kecerdasan Emosional, Self Efficacy, dan Motivasi Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran Akuntansi Keuangan Kelas XI Akuntansi SMK Negeri di Jakarta Timur - Shufaira Nur Faradillah; Ati Sumiati; Achmad Fauzi (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine and explain the influence of emotional intelligence, self-efficacy and learning motivation on student achievement in financial accounting subjects in class XI Accounting at SMK Negeri in East Jakarta. This research is quantitative research with a survey method. The population in this study were students of class XI Accounting at State Vocational Schools in East Jakarta, with an affordable population of 178 students and a total sample of 119 respondents. The sampling technique in this study was proportional random sampling through the isac and michale tables with a significance level of 5%. The results of partial hypothesis testing indicate that the emotional intelligence variable (X1) influences learning achievement (Y). The evidenced by the value of tcount > ttable 2,930 > 1,98081, the self-efficacy variable (X2) has an influence on learning achievement (Y) as evidenced by the value of tcount > ttable (2,061 > 1.99081), learning motivation (X3) influences achievement learning (Y) as evidenced by the value of tcount > ttable (4,410 > 1,99081) and simultaneous hypothesis testing shows that emotional intelligence (X1), self-efficacy (X2), and learning motivation (X3) affect learning achievement (Y) as evidenced by the value of Fcount > Ftable (49.062 > 2.68). Based on the results of this study indicate that there is a positive and significant influence between emotional intelligence and learning achievement. There is a positive and significant influence between self-efficacy and learning achievement. There is a positive and significant influence between learning motivation and learning achievement. And there is a simultaneous influence on student achievement between emotional intelligence, self-efficacy, and learning motivation